Diaphragmatic hernia: an unusual presentation. (23rd April 2013) - Shah, Neha; Fernandes, Roland; Thakrar, Amit; Rozati, Hamoun
Abstract : A 53-year-old lady presented to A&E with a 3-day history of severe epigastric pain and vomiting. This was preceded by a 3-month history of generalised abdominal discomfort, early satiety and increasing shortness of breath. A CT scan showed a left-sided posterior diaphragmatic defect. Urgent repair of the hernia showed herniation of three-quarter of the stomach, half of the transverse colon, the 13 cm spleen and the pancreas in the chest. There were no postoperative complications. Traumatic diaphragmatic hernias are known to be a complication of major trauma. However, the patient in this case report presented acutely, after mild physical trauma related to using a rowing machine. This exercise, when not performed correctly can raise intra-abdominal pressure. It is plausible that this trauma, although mild, was sufficient in causing the lady's diaphragmatic hernia. This case would suggest that the trauma required to cause a diaphragmatic hernia need not be as severe as originally thought.